Multiple functions of the nonstructural protein 3D in picornavirus infection - Xu, Chenxia; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Huang, Juan; Ou, Xumin; Sun, Di; He, Yu; Wu, Zhen; Wu, Ying; Zhang, Shaqiu; Tian, Bin; et al. (Frontiers in Immunology, 2024)
3D polymerase, also known as RNA-dependent RNA polymerase, is encoded by all known picornaviruses, and their structures are highly conserved. In the process of picornavirus replication, 3D polymerase facilitates the assembly of replication complexes and directly catalyzes the synthesis of viral RNA. The nuclear localization signal carried by picornavirus 3D polymerase, combined with its ability to interact with other viral proteins, viral RNA and cellular proteins, indicate that its noncatalytic role is equally important in viral infections. Recent studies have shown that 3D polymerase has multiple effects on host cell biological functions, including inducing cell cycle arrest, regulating host cell translation, inducing autophagy, evading immune responses, and triggering inflammasome formation. Thus, 3D polymerase would be a very valuable target for the development of antiviral therapies. This review summarizes current studies on the structure of 3D polymerase and its regulation of host cell responses, thereby improving the understanding of picornavirus-mediated pathogenesis caused by 3D polymerase.